Low Volume Rural Roads - Mackie, Peter; Nellthorp, John; Laird, James (World Bank, Washington, DC, 2012)
The objective of this note is to advise on an appropriate economic appraisal methodology that should be used for the assessment of Low Volume Rural Roads - that is roads upon which less than 200 motorized vehicles per day travel. Section 1 of this note sets out the reasons that Low Volume Rural Roads require a slightly different consideration from other transport projects. Section 2 discusses the approaches to economic evaluation that can be used for low volume rural roads, whilst Section 3 presents the manner that the consumer surplus method can be extended to account for the characteristics of low volume rural roads. Section 4 contains a summary of the main points of the note.